2019
DOI: 10.21203/rs.2.14157/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence and determinants of Klebsiella species bloodstream infection in the western interior of British Columbia, Canada

Abstract: BACKGROUND Klebsiella species are among the most common causes of bloodstream infection (BSI).However, few studies have evaluated their epidemiology in non-selected populations. The objective was to define the incidence of, risk factors for, and outcomes from Klebsiella species BSI among residents of the western interior of British Columbia, Canada.METHODS Population-based surveillance was conducted between April 1, 2010 and March 31, 2017.RESULTS 151 episodes were identified for an incidence of 12.1 per 100,0… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Nosocomial and community-acquired K. pneumoniae infections, frequently initiated in the oropharynx or intestinal niche, include device-associated contamination, urinary tract diseases, pneumonia, bloodstream infections, and other clinical manifestations. A population surveillance-based study showed that patients with co-morbidities tend to be more susceptible to bloodstream infections, caused by Klebsiella species [2]. Several antibiotic resistant K. pneumoniae strains have been circulating, which constitutes a challenge to treat pathological alterations of patient's tissues infected with one or more ESKAPE species (reviewed in [3]).…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial and community-acquired K. pneumoniae infections, frequently initiated in the oropharynx or intestinal niche, include device-associated contamination, urinary tract diseases, pneumonia, bloodstream infections, and other clinical manifestations. A population surveillance-based study showed that patients with co-morbidities tend to be more susceptible to bloodstream infections, caused by Klebsiella species [2]. Several antibiotic resistant K. pneumoniae strains have been circulating, which constitutes a challenge to treat pathological alterations of patient's tissues infected with one or more ESKAPE species (reviewed in [3]).…”
Section: Introductionmentioning
confidence: 99%